Entrepreneurial Marketing dan Trust Terhadap Marketing Performance - Aditya Liliyan (Universitas Pendidikan Nasional, 2020)
The purpose of this research is to determine the level of entrepreneurial marketing and trust carried out by SMEs and to contribute to literature and conceptual models on the effect of entrepreneurial marketing and trust on marketing performance. The sample in this study were SMEs in the handicraft sector in Rembang, Central Java. The number of samples studied was 200 samples. The sampling technique used purposive sampling. The sample criteria are SMEs that have been running a business for at least 3 (three) years. This is because in measuring the dimensions of marketing performance there are several indicators of the level of achievement of marketing performance each year, at least for a minimum of 3 years it can be seen the marketing performance of these SMEs. Data analysis using multiple regression modeling. The results show that entrepreneurial marketing has a significant effect on marketing performance, trust has a significant effect on marketing performance, entrepreneurial marketing and trust simultaneously have a significant effect on marketing performance.